Ageing perspective on cognitive outcomes from reproductive hormone adjustments - Zhang, Grace; Devo, Perry; O'Leary, Valerie B; Ovsepian, Saak V (Heliyon, 2023)
In addition to primary reproductive functions, gonadal hormones play an important role in an array of neural mechanisms across the human lifespan. The ageing-related decline in their activity has been linked to the deterioration of cognitive functions in otherwise healthy women, associated with menopause transition, contributing to higher incidents of post-menopause dementia. Given the growing utility of gonadal steroids for birth control, as well as for compensatory treatment of menopause and oophorectomy symptoms, and adjuvant transgender therapy, their long-term effects on neural mechanisms warrant comprehensive assessment. In this article, we present an ageing perspective on the cognitive outcomes from contraceptive and replacement therapeutic use of gonadal hormones and discuss their effects on the risk of developing Alzheimer's and Parkinson's dementia. Despite rising data supporting the ameliorative effects of reproductive hormones on cognitive facilities, their impact varies depending on study design and type of intervention, thus, implying dynamic neuro-endocrine interactions with complex compensatory mechanisms. Elucidating differential effects of reproductive hormone adjustments on cognition with underlying mechanisms is expected not only to shed light on important aspects of brain ageing and dementia but to facilitate their use in personalized medicine with improved safety margins and therapeutic outcomes.
Keywords: Transgender; Neuroprotection; Healthy ageing; Contraception; Oestrogen; Cognitive decline; Gender transition; Hormone replacement therapy